The agony of choice: Impact of the host animal species on the enzyme‐linked immunosorbent assay performance for host cell protein quantification. Issue 1 (8th November 2022) - Seisenberger, Christina; Graf, Tobias; Sticht, Sarah; Haindl, Markus; Mohn, Ulrich; Wegele, Harald; Wiedmann, Michael; Wohlrab, Stefanie
Abstract: Host cell proteins (HCPs) are inevitable process‐related impurities in biotherapeutics commonly monitored by enzyme‐linked immunosorbent assays (ELISAs). Of particular importance for their reliable detection are the anti‐HCP polyclonal antibodies (pAbs), supposed to detect a broad range of HCPs. The present study focuses on the identification of suitable host animal species for the development of high‐performance CHO‐HCP ELISAs, assuming the generation of pAbs with adequate coverage and specificity. Hence, antibodies derived from immunization of sheep, goats, donkeys, rabbits, and chickens were compared concerning their amount of HCP‐specific antibodies, coverage, and performance in a sandwich ELISA. Immunization of sheep, goats, donkeys, and rabbits met all test criteria, whereas the antibodies from chickens cannot be recommended based on the results of this study. Additionally, a mixture of antibodies from the five host species was prepared to assess if coverage and ELISA performance can be improved by a multispecies approach. Comparable results were obtained for the single‐ and multispecies ELISAs in different in‐process samples, indicating no substantial improvement for the latter in ELISA performance while raising ethical and financial concerns.